Enake’s Dairy Shop or About Lactobacillus Bulgaricus in Romanian Avant-Garde - Malamir Spasov (Zeszyty Cyrylo-Metodiańskie)
This article presents some notes on the curious case of а Bulgarian migrant family and the way their dairy shop influenced the development of the Romanian avant-garde art movement. In the 1990s and 2000s, the National Theatre building in Bucharest housed a fabled pub called Enake’s Dairy Shop, which sheltered part of the Romanian artistic underground. The name came from an actual dairy shop that turned into a cornerstone of the Romanian capital’s artistic underground between the World Wars. The original dairy shop was established by a family of Bulgarian peasants, refugees from Western Macedonia, who settled in Bucharest in the 1900s. While working in his father Yanaki (Enake)’s Dairy shop, young Georgi began to write avant-garde poetry under the pseudonym Stephan Roll. Gradually, their dairy shop became a regular meeting place for a large number of young Romanian avant-garde artists in interwar Bucharest and one of the most original literary circles in Romania. Some of the most distinguished editions of the Romanian avant-garde were created there. This name brings together the avant-garde currents in the two countries, mostly through a young avant-garde author like Georgi Dinev / Stephan Roll, for whom there were no borders, both literally and figuratively. Original title in Bulgarian: „Млекарницата на Енаке“ или за Lactobacillus bulgaricus в румънския авангардизъм.